(untitled) (Swiss Medical Weekly, 2015)
QUESTIONS UNDER STUDY: Many persons are travelling all over the world; the elderly with pre-existing diseases also travel to places with less developed health systems. Reportedly, fewer than 0.5% of all travellers need repatriation. We aimed to analyse and examine people who are injured or ill while abroad, where they travelled to and by what means they were repatriated. METHODS: Retrospective cross-sectional study with adult patients repatriated to a single level 1 trauma centre in Switzerland (2000–2011). RESULTS: A total of 372 patients were repatriated, with an increasing trend per year. Of these, 67% were male; the median age was 56 years. Forty-nine percent sustained an injury, and 13% had surgical and 38% medical pathologies. Patients with medical conditions were older than those with injuries or surgical emergencies (p <0.001). Seventy-three percent were repatriated from Europe. For repatriation from Africa trauma was slightly more frequent (53%, n = 17) than illnesses, whereas for most other countries illnesses and trauma were equally distributed. Injured patients had a median Injury Severity Score of 8. The majority of illnesses involved the nervous system (38%), mainly stroke. Forty-five percent were repatriated by Swiss Air Ambulance, 26% by ground ambulance, 18% by scheduled flights with or without medical assistance and two patients injured near the Swiss boarder by helicopter. The 28-day mortality was 4%. CONCLUSIONS: The numbers of travellers repatriated increased from 2000 to 2011. About half were due to illnesses and half due to injuries. The largest group were elderly Swiss nationals repatriated from European countries. As mortality is relatively high, special consideration to this group of patients is warranted.